Effectiveness Comic Media Education in Prevention Violence towards Children - Siti Mardiyah; Nurul Devi Ardiani; Aris Prastyonhngsih (International Journal of Public Health Excellence (IJPHE), 2023)
Violence against children is treatment, action, or neglect that results in disability and death in children. Children need to have sufficient knowledge of violence and its prevention so that they can minimize and prevent and protect themselves from violence. Efforts to increase prevention of violence against children can be implemented by increasing knowledge. One way to increase knowledge is to use learning methods using comics. Comics are educational media with interesting pictures and stories that are easy for children to understand. The benefit of research is to gain knowledge so that you are able to prevent and protect yourself against violence against children. The research method was carried out using comic media on elementary school children. The results of the study after education was carried out, namely that there was an increase in children's knowledge about the knowledge of preventing violent behavior.